18F-FDG PET and Bone Scintigraphy of Epithelioid Hemangioendothelioma. (February 2019) - Hubaut, Marc-Antoine; Jaillard, Alice; Eloy, Capucine; Petyt, Gregory
Abstract : Abstract: We report the case of a 31-year-old woman with left foot bones located epithelioid hemangioendothelioma. It is a rare type of vascular tumor, locally aggressive with metastatic potential. It was revealed by a chronic isolated left foot pain. Conventional imaging showed multiple osteolytic lesions of the bones, appearing aggressive. Both bone scintigraphy and 18 F-FDG PET showed an increased uptake of these lesions and confirmed the limited extent to distal extremity of the left lower limb. Final diagnosis was given on a surgical biopsy. Patient was treated by hyperthermic chemotherapy using isolated limb perfusion.